Improving the assessment of polluted sites using an integrated bio-physico-chemical monitoring framework. (March 2022) - Garg, Anuradha; Yadav, Brijesh K.; Das, Diganta B.; Wood, Paul J.
Abstract: Soil – water pollution resulting from anthropogenic activities is a growing concern internationally. Effective monitoring techniques play a crucial role in the detection, prevention, and remediation of polluted sites. Current pollution monitoring practices in many geographical locations are primarily based on physico–chemical assessments which do not always reflect the potential toxicity of contaminant 'cocktails' and harmful chemicals not screened for routinely. Biomonitoring provides a range of sensitive techniques to characterise the eco–toxicological effects of chemical contamination. The bioavailability of contaminants, in addition to their effects on organisms at the molecular, cellular, individual, and community level allows the characterisation of the overall health status of polluted sites and ecosystems. Quantifying bioaccumulation, changes to community structure, faunal morphology, behavioural, and biochemical responses are standard procedures employed in biomonitoring studies in many High-Income Countries (HICs). This review highlights the need to integrate biomonitoring tools alongside physico–chemical monitoring techniques by using 'effect–based' tools to provide more holistic information on the ecological impairment of soil-water systems. This paper considers the wider implementation of biomonitoring methods in Low to Middle Income Countries (LMICs) and their significance in pollution investigations and proposes an integrated monitoring framework that can identify toxicity drivers by utilising 'effect–based' and 'risk–based' monitoring approaches. Graphical abstract: Image 1 Highlights: Low to Middle Income Countries require robust and cost-effective monitoring methods. Pollution monitoring practises can be improved by incorporating biomonitoring. Biomonitoring bridges information between chemical analysis and ecosystem health. Biomonitoring allows the comparison of effects in various ecosystem compartments. A framework for implementation of integrated pollution monitoring is proposed.